2014
DOI: 10.1007/s11069-014-1184-6
|View full text |Cite
|
Sign up to set email alerts
|

Main issues of an evacuation in case of volcanic crisis: social stakes in Guadeloupe (Lesser Antilles Arc)

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
0
8
0
2
Order By: Relevance
“…The importance of volcano research is underscored by a number of studies that have examined volcano risk perception, the extent of hazard adjustment adoption, or both (e.g., [21,42,79,92]). In addition, other researchers have studied volcano risk communication (e.g., [5,6,10,35]) and evacuation (e.g., [11,68,70]). However, few volcano studies have explored a broad range of variables involved in the adoption of volcano hazard adjustments.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of volcano research is underscored by a number of studies that have examined volcano risk perception, the extent of hazard adjustment adoption, or both (e.g., [21,42,79,92]). In addition, other researchers have studied volcano risk communication (e.g., [5,6,10,35]) and evacuation (e.g., [11,68,70]). However, few volcano studies have explored a broad range of variables involved in the adoption of volcano hazard adjustments.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it can be estimated that the recent lahars of the Prêcheur River in Martinique took about 15 minutes to reach the coastal road after six kilometers of travel. Furthermore, several sociological surveys on human perception and volcanic risks undertaken in Guadeloupe and Martinique over the last two decades have shown that a majority of the population questioned would leave exposed areas, in a spontaneous manner, as soon as the first signs of an eruption were perceived (D'Ercole and Rançon 1994; Leone and Lesales 2009;Mas 2012;Chenet et al 2014). This is precisely what happened in Guadeloupe on 8th July 1976 at 8:55 am during the first phreatic explosion of La Soufrière, which plunged Saint-Claude into darkness for 20 minutes due to the ashfall (Feuillard et al 1983;Feuillard 2011;Hincks et al 2014).…”
Section: Discussion: Contributing To Evacuation Planningmentioning
confidence: 99%
“…Virginie Duvat soulignait dès 2008, à propos de Saint-Martin, l'extrême fragilité des Saint-Martinois et pointait le rôle de la fragmentation socio-culturelle et des disparités économiques (Duvat, 2008). Les îles de l'archipel Guadeloupéen et Saint-Martin accusent toujours un différentiel de développement par rapport à la moyenne nationale française (Chenet et al, 2014 ;Goujon et Hoarau, 2015). Les inégalités de développement entraînent des processus d'exclusion, de marginalisation et augmentent la précarité des conditions de vie au quotidien.…”
Section: La Culture Du Risque à L'épreuve Des Discours Des Acteurs Guadeloupéensunclassified
“…Enfin, plusieurs analyses soulignent l'importance de l'insularité et de la distance, qui constituent des freins pour l'envoi des secours et la gestion de crise (Chenet et al, 2014 ;Leone et al, 2018). Dans le cas de Saint-Martin, la Désirade, les Saintes ou Marie-Galante, on parle même de double-insularité (Nicolas, 2005a(Nicolas, et 2005bDuvat, 2008 ;, voire « d'hyper-insularité » (Taglioni, 2011).…”
Section: La Culture Du Risque à L'épreuve Des Discours Des Acteurs Guadeloupéensunclassified